RNA as the stone guest of protein aggregation. Issue 21 (17th October 2020) - Louka, Alexandra; Zacco, Elsa; Temussi, Piero Andrea; Tartaglia, Gian Gaetano; Pastore, Annalisa
Abstract: The study of prions as infectious aggregates dates several decades. From its original formulation, the definition of a prion has progressively changed to the point that many aggregation-prone proteins are now considered bona fide prions. RNA molecules, not included in the original 'protein-only hypothesis', are also being recognized as important factors contributing to the 'prion behaviour', that implies the transmissibility of an aberrant fold. In particular, an association has recently emerged between aggregation and the assembly of prion-like proteins in RNA-rich complexes, associated with both physiological and pathological events. Here, we discuss the historical rising of the concept of prion-like domains, their relation to RNA and their role in protein aggregation. As a paradigmatic example, we present the case study of TDP-43, an RNA-binding prion-like protein associated with amyotrophic lateral sclerosis. Through this example, we demonstrate how the current definition of prions has incorporated quite different concepts making the meaning of the term richer and more stimulating. An important message that emerges from our analysis is the dual role of RNA in protein aggregation, making RNA, that has been considered for many years a 'silent presence' or the 'stone guest' of protein aggregation, an important component of the process.